Necessary Conditions for the Existence of Global Solutions to Nonlinear Fractional Differential Inequalities and Systems - Ibtisam Aldawish; Bessem Samet (Journal of Function Spaces)
In this paper, fractional differential inequalities and systems of fractional differential inequalities involving fractional derivatives in the sense of Caputo are investigated. Namely, necessary conditions for the existence of global solutions are obtained. Our approach is based on the test function method and some integral inequalities.